Land structure and concentration in the Cantuquiriguaçu/PR territory: historical problems and recent dynamics - Krajevski, Luis Claudio (2022)
The Cantuquiriguacu Territory (translation for Território da Cidadania Cantuquiriguaçu) is a region of lower socioeconomical indicators in relation to the State of Parana’s averages. Therefore, this paper aims to approach the land structure’s characteristics in the Cantuquiriguacu Territory, as well as its changes throughout the 2006-2017 period, a temporal hiatus that comprises the last two agriculture and livestock census. The methodological procedures adopted in the research consist of bibliographical and documental reviews, in addition to the use of statistic data, especially the ones published by the Brazilian Institute for Geography and Statistics (translation for Instituto Brasileiro de Geografia e Estatística - IBGE), and by the Paranaense Institute for Economic and Social Development (translation for Instituto Paranaense de Desenvolvimento Econômico e Social - IPARDES). The results present a land concentration increase in the region, indicated by a high-to-very-high concentration in 80% of the region’s municipalities.